The “A to Z” of Managing Type 2 Diabetes in Culturally Diverse Populations - Caballero, A. Enrique (Frontiers in Endocrinology, 2018)
Type 2 diabetes affects racial/ethnic minorities at an alarming rate in the US and in many countries around the world. The quality of health care provided to these groups is often suboptimal, resulting in worse patient-related outcomes when compared to those in mainstream populations. Understanding the complex biological factors that influence the development and course of the disease in high-risk populations is extremely important but often insufficient to implement effective prevention and treatment plans. Multiple factors must be addressed in routine diabetes clinical care. This paper discusses various key factors, organized in alphabetical order. These factors are acculturation, biology, clinician’s cultural awareness, depression and diabetes-specific emotional distress, educational level, fears, group integration, health literacy, intimacy and sexual dysfunction, judging, knowledge of the disease, language, medication adherence, nutritional preferences, other forms of medicine (alternative), perception of body image, quality of life, religion and faith, socio-economic status, technology, unconscious bias, vulnerable groups, asking why?, xercise, “you are in charge” and zip it! Considering these factors in the development of type 2 diabetes prevention and treatment programs will help improve diabetes-related outcomes in culturally diverse populations and reduce health care disparities.